Cassava drying industries: New potential for the Caribbean - Reeves, J. (1985)
The evolution of cassava drying industries on the northern coast of Colombia, as a result of a joint effort of CIAT/Colombian agencies, is discussed; projections for other Caribbean countries are included. It is stressed that the establishment of a cassava drying pilot plant would yield real data to determine the feasibility of a large-scale project. Cassava potential in Jamaica is briefly analyzed. (CIAT)